Black Umbrellas for the Republic: The Thursday Protest Movement (Aksi Kamisan) in Jakarta and the Monument of Memory of the Semanggi I Tragedy - Wayan Adrian; Tuty Maryati; I Putu Hendra Mas Martayana (Local History & Heritage, 2026)
This study investigates Aksi Kamisan as a form of resistance to the collective forgetting of the Semanggi I Tragedy and examines its potential as a historical learning resource in schools. The research addresses how Aksi Kamisan preserves public memory of past human rights violations and how its values can be integrated into history education. Employing a qualitative social history approach, data were collected through interviews, observations, and document analysis, and interpreted using Pierre Nora’s concept of sites of memory, Benedict Anderson’s theory of imagined communities, and the concept of mass action. The findings reveal that Aksi Kamisan functions as a non-physical site of memory that sustains collective remembrance through symbolic practices, ritualized public gatherings, and the continued presence of peaceful demonstrations. The black umbrella and the strategic use of social media have fostered a cross-regional imagined community grounded in moral solidarity and shared concern for justice. The movement also represents a distinctive form of mass action characterized by its peaceful, consistent, and memory-oriented nature. In the educational sphere, Aksi Kamisan offers significant value for teaching contemporary history and human rights by encouraging critical thinking, empathy, democratic awareness, and reflection on justice. The study concludes that Aksi Kamisan serves not only as symbolic resistance against forgetting but also as a reconciliation-oriented effort based on truth-seeking and equitable restoration.